Tinjauan Akuntansi Aset Tak Berwujud dalam Industri Sepak Bola di PT Bali Bintang Sejahtera Tbk Review of - Muh. Fachrul Muzawwir; Vina Arnita (Mahesa Research Center, 2023)
Football is the most popular sport in the world. Its popularity makes football a professional industry that generates trillions of rupiah. This rapid development requires the football team to pay attention to its accounting records. One of the most important assets to pay attention to in accounting for a football team is players and team officials, which are classified as intangible assets. This study aims to determine and understand the accounting treatment of football team players and officials and to determine the suitability of their treatment with the Statement of Financial Accounting Standards Number 19 regarding intangible assets. The research object chosen was the first football team to become a public company in Indonesia, PT Bali Bintang Sejahtera Tbk or Bali United FC. The accounting treatments discussed include general policies, initial recognition and measurement, measurement after initial recognition, amortization, impairment, derecognition, disposal, and disclosure. The method used in collecting data is literature study and secondary data in the form of the 2019 Financial Statements of PT Bali Bintang Sejahtera Tbk. The intangible assets in the form of players and team officials at PT Bali Bintang Sejahtera Tbk are called registration. Based on the results of the study, it can be concluded that the accounting treatment of players and team officials at PT Bali Bintang Sejahtera Tbk is in accordance with Statement of Financial Accounting Standards Number 19.